Theoretical Study on Internal Forces of Primary Support of Tunnel by considering Time Effect - Zhuangzhi Yang; Yuqing Wang; Lin Song; Xinyu Wang (Advances in Materials Science and Engineering)
Understanding the internal force distribution and prejudging the weak part of tunnel supporting structure under complicated construction surroundings have become one of the important measures to ensure the safety of tunnel construction. Based on the initial parameter method and field-monitoring results of surrounding rock pressure, the theory of beam on elastic foundation is employed to derive the analytical solution of primary support internal forces. By combining the monitored data of rock pressure in one tunnel, solution of primary support internal force of a section is back analyzed and weak parts of the primary support are analyzed and evaluated. The results show that, after the tunnel excavation is completed, the internal forces of the primary support of the tunnel arch grow larger over time. When θ > 1.0, the internal forces change greatly. The internal force of the primary support decreased to different extents within 2 days after the primary support was applied and then gradually increased over time. Considering the situationality and changeability of the tunnel construction process, the analytical solution for the primary support internal forces of a multicenter arch tunnel proposed in this paper has a strong feasibility in tunnel construction. The conclusions obtained here could provide theoretical support for the design of supporting structure and the optimization of tunnel construction technology.